Philosophy of living on earth in One Piece - Gonçalves, Laís (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2024)
Ayn Rand, American philosopher and novelist, idealized Objectivism which, in her words, is a philosophy for living on Earth. Her philosophy is based on individualism, capitalism and selfishness, having a unique and objective reality independent of subjective concepts, such as feelings and desires. One Piece, a Japanese work, does not have any explicit relationship with ideological and philosophical concepts. However, anime can easily be associated with existing concepts in objectivist philosophy. In this sense, the interpretation of values, individualism, the search for one's own happiness and selfishness are present during a moment of leisure, when watching the work of One Piece, and which represents Rand's philosophy even after years of its idealization. Therefore, follow the journey full of moments of companionship, determination, freedom and reflections on humanity in a fictional narrative mixed with knowledge from Ayn Rand.